Pluralisme Hukum dan Legitimasi Kultural: Menata Ulang Hukum Adat Sasak untuk Mencegah Perkawinan Anak di Lombok - Muhammad Suhardi (Society, 2025)
Child marriage remains a deeply rooted socio-cultural issue in Lombok, West Nusa Tenggara, where traditional customs, religious authority, and economic hardship intersect. This study investigates how Sasak customary law (awiq-awiq) and the roles of local religious figures, Kyai and Tuan Guru, contribute to both the persistence and potential transformation of early marriage practices. Using a qualitative approach involving interviews, participant observation, and document analysis across three regencies, Central Lombok, West Lombok, and East Lombok, the research finds that cultural traditions such as merarik kodeq (a customary elopement practice) are still widely accepted as mechanisms to preserve family honor and reduce economic burden. Although national legal frameworks, specifically Law No. 16 of 2019 on Marriage and West Nusa Tenggara Regional Regulation No. 5 of 2021 on the Prevention of Child Marriage, set a minimum legal age of 19, implementation remains weak due to widespread use of religious court dispensations and cultural resistance. Findings show that while some customary and religious leaders continue to legitimize child marriage, an increasing number have begun to reinterpret awiq-awiq in line with contemporary health, educational, and religious considerations. Village-level forums (musyawarah desa) are emerging as strategic spaces for negotiating alignment between formal legal norms and local wisdom. This study develops a culturally embedded integration model that emphasizes participatory governance, moral legitimacy, and the co-production of legal norms. It offers empirical insight into the resilience of early marriage in culturally entrenched settings. It contributes a conceptual model for rethinking legal pluralism as a framework for reform through collaboration, not confrontation. These findings expand current scholarship by repositioning customary and religious authority as key agents in adaptive and community-driven legal transformation.